Identification, structural, and biochemical characterization of a group of large Csn2 proteins involved in CRISPR-mediated bacterial immunity - Lee, Kwang-Hoon; Lee, Seong-Gyu; Lee, Kyung Eun; Jeon, Hyesung; Robinson, Howard; Oh, Byung-Ha (WILEY-BLACKWELL, 2012)
Many prokaryotic organisms acquire immunity against foreign genetic material by incorporating a short segment of foreign DNA called spacer into chromosomal loci, termed clustered regularly interspaced short palindromic repeats (CRISPRs). The encoded RNAs are processed into small fragments that guide the silencing of the invading genetic elements. The CRISPR-associated (Cas) proteins are the main executioners of these processes. Herein, we report the crystal structure of Stu0660 of Streptococcus thermophilus, a Cas protein involved in the acquisition of new spacers. By homotetramerization, Stu0660 forms a central channel which is decorated with basic amino acids and binds linear double-stranded DNA (dsDNA), but not circular dsDNA. Despite undetectably low sequence similarity, two N-terminal domains of Stu0660 are similar to the entire structure of an Enterococcus faecalis Csn2 protein, which also forms a homotetramer and binds dsDNA. Thus, this work identifies a previously unknown group of Stu0660-like Csn2 proteins (similar to 350 residues), which are larger than the known canonical Csn2 proteins (similar to 220 residues) by containing an extra C-terminal domain. The commonly present central channel in the two subgroups appears as a design to selectively interact with linear dsDNA. Proteins 2012. (c) 2012 Wiley Periodicals, Inc.